Comparative Religion - Bouquet, A. C. (Alan Coates) (Harmondsworth, Eng., Baltimore Penguin Books, 1967)
The author writes with scientific impartiality and with full recognition of recent developments in the acquisition of knowledge: and he believes that there is only one right way of persuading, and that is to present what is true in such a way that nothi
Keywords: Religions